2008
DOI: 10.1097/cad.0b013e3282f24031
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants block proteasome inhibitor function in endometrial carcinoma cells

Abstract: We have recently demonstrated that proteasome inhibitors can be effective in inducing apoptotic cell death in endometrial carcinoma cell lines and primary culture explants. Increasing evidence suggests that reactive oxygen species are responsible for proteasome inhibitor-induced cell killing. Antioxidants can thus block apoptosis (cell death) triggered by proteasome inhibition. Here, we have evaluated the effects of different antioxidants (edaravone and tiron) on endometrial carcinoma cells treated with aldehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 22 publications
1
40
0
1
Order By: Relevance
“…As noted above, proteasome inhibitors can induce significant oxidative stress (ROS); furthermore, cells exposed to proteasome inhibitors can be rescued by various antioxidants, including NAC (Ling et al, 2003;Fribley et al, 2004;Minami et al, 2005;Llobet et al, 2008). Moreover, proteasome inhibitors can also induce Bax and JNK activation (Dai et al, 2003;Dewson et al, 2003;Yu et al, 2003;Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…As noted above, proteasome inhibitors can induce significant oxidative stress (ROS); furthermore, cells exposed to proteasome inhibitors can be rescued by various antioxidants, including NAC (Ling et al, 2003;Fribley et al, 2004;Minami et al, 2005;Llobet et al, 2008). Moreover, proteasome inhibitors can also induce Bax and JNK activation (Dai et al, 2003;Dewson et al, 2003;Yu et al, 2003;Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Many other studies have probed the role of ROS in bortezomib-induced cell death in model systems, including myeloma (83), mantle cell lymphoma (85), and leukemia (71), as well as solid tumor models like colon cancer (72), endometrial cancer (62), and head and neck squamous cell carcinoma (29). Across the hematologic malignancy models, the ability of bortezomib to increase ROS appears conserved, with a number of different antioxidants, such as NAC, showing cytoprotection.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…Importantly, earlier studies have shown that vitamin C blocks the activity of bortezomib in vitro by its direct binding to bortezomib. [25][26][27] In addition, production of reactive oxygen species by bortezomib 28 is reduced by vitamin C. 29 However, the clinical significance of vitamin C intake in MM patients receiving bortezomib treatment remains unclear. Our study confirms that vitamin C as a dietary supplement can inhibit anti-MM activity of bortezomib in vivo.…”
Section: Introductionmentioning
confidence: 99%